A novel fully-human cytolytic fusion protein based on granzyme B shows in vitro cytotoxicity and ex vivo binding to solid tumors overexpressing the epidermal growth factor receptor. Issue 2 (1st May 2016) - Niesen, Judith; Hehmann-Titt, Grit; Woitok, Mira; Fendel, Rolf; Barth, Stefan; Fischer, Rainer; Stein, Christoph
Highlights: Characterization of a fully human EGFR-specific scFv-granzyme B fusion protein. Specific in vitro and ex vivo binding of GbR201 K-scFv1711 to EGFR + solid tumor cells. It induced antigen-specific cytotoxic and pro-apoptotic effects in solid tumor cells. Chloroquine enhanced cytotoxic potential of GbR201 K-scFv1711. Abstract: Human cytolytic fusion proteins (hCFPs) offer a promising immunotherapeutic approach for the treatment of solid tumors, avoiding the immunogenicity and undesirable side-effects caused by immunotoxins derived from plants or bacteria. The well-characterized human serine protease granzyme B has already been used as a therapeutic pro-apoptotic effector domain. We therefore developed a novel recombinant hCFP (GbR201K-scFv1711) consisting of an epidermal growth factor receptor-specific human antibody fragment and a granzyme B point mutant (R201K) that is insensitive to serpin B9 (PI9), a natural inhibitor of wild-type granzyme B that is often expressed in solid tumors. We found that GbR201K-scFv1711 selectively bound to epidermoid cancer and rhabdomyosarcoma cells and was rapidly internalized by them. Nanomolar concentrations of GbR201K-scFv1711 achieved the specific killing of epidermoid cancer cells by inducing apoptosis, and similar effects were observed in rhabdomyosarcoma cells when GbR201K-scFv1711 was combined with the endosomolytic substance chloroquine. The novel hCFP was stable in serum and bound to human rhabdomyosarcoma tissue ex vivo . These data confirm that GbR201K-scFv1711 is a promising therapeutic candidate suitable for further clinical investigation.